Survival of Scylla serrate Larvae reared in large tanks with different salinities. - Perono, Irvin R.
A study was conducted to determine if salinity (20ppt and 30 ppt) of the rearing water would affect survival of the zoea larvae of S. serrata reared in four 1,000 L circular and 2 rectangular 500 L containers. Bacterial analysis of the rearing water was also monitored during the duration of the experiment. In another experiment, survival and metamorphosis of megalopa was determined using 35 ppt, 25 ppt, 20 ppt, 15 ppt, and 10 ppt salinity levels. Circular plastic containers with a volume of 3.5 L were filled with 3 L water. Aeration was provided and net was added as shelter. Larvae were fed with Artemia, at 5 ind / ml. Daily transfer of megalopa from one container to another was done., Results showed that in 30 ppt treatment mean percent survival (9.7percent - 28.6percent in Z1 to Z2 and 2.3 percent - 8.0 percent in Z2 to Z3), was higher compared with 20 ppt treatment (9.9percent - 25.2percent Z1 to Z2 and 1.6percent -3.6percent in Z2 to Z3). Metamorphosis was higher in two treatments, 97 percent in 20 ppt and 100percent in 30 ppt from Z1 to Z2; 87percent in 20 ppt and 92 percent in 30 ppt Z2 to Z3. However statistical analysis showed that there was no significant difference in the mean percent survival and metamorphosis of the larvae in two treatments . There was high bacterial count which exceeded the required normal level (10 raise to the 2nd power cfu /ml). Luminous bacteria was higher in 30 ppt treatment (4.513 x 10 raise to the 3rd power cfu / ml) than in 20 ppt (5.400 x 10 raise to the 2nd power cfu / ml). For the megalopa salinity tolerance experiment, there was higher survival of 30 percent 97percent in 20-35 ppt and lower in 10 - 15 ppt (0 percent - 6.7 percent0. All the megalopa survived 15 ppt -35 ppt molted into crablets.